Optimalisasi Portofolio Saham LQ-45 menggunakan Model Indeks Tunggal dan Pengukuran Value at Risk dengan Variance Covariance - Yoga Perdana; Dony Permana; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2018)
Abstract – Investments are placing a current amount of funds with the aim of making a profit in the future. The problem faced by investors is to determine which assets should be selected to obtainmaximum profit and minimum losses. This research aims to determine the amount of proportion of funds invested into the optimal portfolio and to know the value of Value at Risk (VaR) on stocks that go into the optimal portfolio. Based on research on LQ-45 stock group found 15 stocks enter into the optimal portfolio from 45 shares of the company. Bank Tabungan Negara (Persero) Tbk. (BBTN) has proportion 18.01% as the largest propotion of funds. Based on the calculation of VaR in the optimal portfolio, obtained VaR value of 8,747,069, which means if investors invest funds in the portfolio of Rp 100,000,000.00 maximum losses to be suffered by investors with 95% confidence level will not exceed Rp 8,747,069.00.